Hearing and Children with Autism Spectrum - Shaima Abd Muhsin AL-Haboobi 1, Sadiq Sahib Hadi Hussain Al-Amin2 , Zainab Abed Muhsin AL-Haboobi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Through the results obtained, we found that most of the families who had a child with autistic disorder wereresidents of cities, with a percentage of 89.8%, while 10.2% who had a child with autism from rural housing.The majority of children with autism had a weak physical condition of 74.5% percent, and 15.3% percenthad an average condition, while 10.2% percent had a good physical condition. Likewise, among the resultsthat we found that the best way to deal with a child with autism is care and treatment, and by 62.2%% and31.6%% of mothers, the opinion was that the best way to deal with a child with the autism spectrum is careonly and by 6% of Among the mothers said that treatment is better than the way they deal with their children.Likewise, between research, autistic children who are taken in the research suffer from a hearing disorderand 82.7% of children respond when their names are heard, while 17.3% do not respond when calling theirnames. It is noticeable that the proportion of children who suffer from hearing loss, 17.3% that they did notrespond when calling their names83.7.% of autistic children asked for help in their daily problems, while16.3% of the children does not asked for help. 53.1% of the children find it difficult to express their wisheswhen they want to ask for something, while, 46.9% of the children did not find it difficult to express whenthey wanted to get something. The research also addressed the behavior of autistic children.